The right and duty of European Works Councils to report back to the workforce: broad uptake, little specificity - De Spiegelaere, Stan; Jagodziñski, Romuald (Brussels, 2016)
"This policy brief examines if and how the reformulated obligation in the Recast European Works Council Directive to report back found its way into EWC agreements by looking at survey data, results of large-scale agreement analysis and by providing examples of clauses in which this obligation is reflected.